Child abuse and neglect in the Arab Peninsula. - Al-Mahroos, Fadheela T. (Saudi Medical Journal, 2007)
OBJECTIVES: To provide an overview of the problem and patterns of child abuse and neglect in the 7 countries of the Arab Peninsula, and to highlight some of the difficulties and shortcomings.METHODS: This study was conducted by reviewing medical literature, published between January 1987 and May 2005. In addition, reports were obtained from regional meetings and professional organizations. Each study or report was reviewed, assessed, and summarized.RESULTS: Three studies from Kuwait identified 27 children; 22 with physical abuse, 3 with sexual abuse, and 2 with Munchausen's syndrome by proxy (MSP), and 3 deaths. Eleven case reports from Saudi Arabia identified 40 abused children; 24 with physical abuse, 6 with sexual abuse, 4 with MSP, and 6 with neglect. Fatal outcome was documented in 5 children. In Oman, 5 cases of MSP were reported. A total of 150 hospital-based cases were reported from Bahrain; 50 with physical abuse, 87 with sexual abuse, and 10 with both forms of abuse. In Yemen, population based surveys revealed a wide spread use of corporal punishments and cruelty to children at homes, schools, and juvenile centers, which ranged from 51-81%.CONCLUSIONS: Children in the Arab Peninsula are subjected to all forms of child abuse and neglect. Child abuse is ignored or may even be tolerated and accepted as a form of discipline, abused children continue to suffer and most abusers go free, unpunished and untreated. Confronting these realities is a necessary step in the long and hard road to break silence, respond to and prevent child abuse and neglect in the Arab Peninsula.